A PERFORMANCE ANALYSIS OF DIFFERENT ATTACHED WAVELENGTHS BASED WDM-ROF SYSTEM FOR FRONTHAUL 5G COMMUNICATION - Aqeel Al-Hilali; Haitham Bashar; Mohammed Abdul Majeed; Ayad Ghany; Hussein Alaa Diame (Journal of Mechanics of Continua and Mathematical Sciences, 2025)
In 5G communication networks, the use of Dense Wavelength Division Multiplexing Radio over Fiber (DWDM-RoF) technology has produced several benefits, including cost savings, increased capacity, and faster data rates. This thesis uses Opti System software version 17.1 to illustrate the design performance of three (DWDM-RoF) systems. Systems with eight, sixteen, and thirty-two channels with a 40 Gbps data bit rate per channel have been suggested, using the Mack Zander Modulator (MZM) as an external modulator. The system's chosen wavelengths fell between 1527.99 and 1565.496 nm in wavelength range, with 1.6 nm separating each pair of channels. Thus, this choice was made in light of the fiber optic's reduced optical signal losses as well as the greater gain spectra of the above-mentioned Erbium Doped Fiber Amplifier (EDFA). The systems' quality factor and minimal bit error rate (BER) were chosen as assessment metrics based on the variations in distances (60, 120, and 180 kilometers). While the BER findings ranged from 3.39e-21 to 2e-100, the Quality Factor results fell between 9.3 (channel 4 at 180 km from the 8-channel system) to 25 (channel at 60 km from the 32-channel system). Analyzing data points to a system with improved performance approaching 320 Gbps. The three suggested technologies can transmit data at speeds of 640 Gbps and 1.28 Tbps, respectively. The non-uniformity of the EDFA gain spectra and the non-uniformity of the fiber optic losses at various wavelengths were the causes of the difference in Quality Factor values and BER for different channels. Additionally, there is a noticeable improvement in the system's performance when the laser's output power is increased from 0 dBm to 5 dBm. Consequently, the system capacity that was attained with a high-quality signal was deemed to be very supportive of the 5 G communication network's needs.